2020
DOI: 10.3390/genes11020222
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel FAM20C Variants in a Family with Raine Syndrome

Abstract: Two siblings from a Mexican family who carried lethal Raine syndrome are presented. A newborn term male (case 1) and his 21 gestational week brother (case 2), with a similar osteosclerotic pattern: generalized osteosclerosis, which is more evident in facial bones and cranial base. Prenatal findings at 21 weeks and histopathological features for case 2 are described. A novel combination of biallelic FAM20C pathogenic variants were detected, a maternal cytosine duplication at position 456 and a paternal deletion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 68 publications
(149 reference statements)
2
18
0
Order By: Relevance
“…So far, no clear relation between the type or location of variants and disease severity has been identified. However, based on our observation, the cases reported and the recent family described by Hernández-Zavala et al, 41 we can suggest that the biallelic proteintruncating mutations were associated with a severe and lethal RS. This was also evident in the two cases with lethal phenotype and have large chromosomal deletions encompassing the entire FAM20C…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…So far, no clear relation between the type or location of variants and disease severity has been identified. However, based on our observation, the cases reported and the recent family described by Hernández-Zavala et al, 41 we can suggest that the biallelic proteintruncating mutations were associated with a severe and lethal RS. This was also evident in the two cases with lethal phenotype and have large chromosomal deletions encompassing the entire FAM20C…”
Section: Discussionsupporting
confidence: 62%
“…Prenatal diagnosis of RS is challenging as most of the patients reported with RS were discovered retrospectively after postnatal diagnosis of the syndrome showing the specific facial dysmorphic features as flat facial profile, hypoplastic nose, and prominent eyes, in addition to intracerebral calcification. 5,9,23,38,41 Thirty-five lethal cases (including this report) 1,3,5-7,21-41 and 22 non-lethal cases with significant variability in the severity have been reported. [8][9][10][11][12][13][14][15][16][17][18][19][20] In our series, we highlight our experience with the prenatal detection of three lethal RS that was suspected as early as the 22 weeks of gestation following the detection of the characteristic craniofacial dysmorphic features, osteosclerosis, and ectopic calcification in the brain and other organs.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…We found that MeCP2 binds to genes in MCF7 cells in regions where CpG methylation had been mapped such as SDK1, a cell adhesion molecule; Jagged 2 (JAG2), a Notch ligand; glycogenin 2 (GYG2), an enzyme involved in glycogen synthesis ( Figure 1C , Figure S1C ). These novel MeCP2 targets as well as others in Figure S1 had not previously been linked with MeCP2, but have been linked with pathobiology associated with cancer ( 76 84 ) or genetic disorders such as Leigh syndrome ( 85 ) and Raine syndrome ( 86 , 87 ). We also found that MeCP2 binds to genomic regions devoid of CpG methylation such as for USP34, MGAM, GMDS, SLC45A4, SSU72, CAPN2 and PLXN2 ( Figures S1B–C ).…”
Section: Resultsmentioning
confidence: 90%